Theme and Symbol in Tennyson's Poems to 1850 - Ryals, Clyde de L. (University of Pennsylvania Press, 2016)
In this book, the author shows how Tennyson became the mental voyager exploring both the inner and outer worlds and, further, how in making the two voyages he followed the pattern of development of other Romantic artists of the nineteenth century.